Phonological Rules on Tamil Language Absorption into Bahasa Indonesia (Study of Transformational Generative Phonology) - Linda Aprillianti (Universitas PGRI Semarang, 2018)
Phonology of Tamil language and Indonesia is very different. Several words are loanwords that are taken from Tamil language. Approximately 30 loanwords of Indonesian are taken from Tamil language. It is possible phonological changes occurred when the words is absorbed into Indonesian language. This study aims to investigate phonological changes that occur in the process of Tamil language absorption into Indonesia language and explains the phonological rules of the changes sound. In this study the writer uses the list of loanwords contained in the article owned by Russel Jones entitled “Loan Word in Contemporary Indonesia”. In method of collecting data, the writer is using noting technique and observation. Then in analyzing the data, the writer uses theory of transformational generative phonology .The result of this study proves that in a loanword there is more than one sound change. The writer found vocal and consonant sound changes in the process of Tamil absorption. There are three types of vocal changes sound; they are assimilation vocal sound, deletion vocal sound and coalescence of vocal sound. Therefore, in consonant sound changes the writer found only two types of sound changes; they are assimilation consonant and deletion consonant. The writer hopes this study will be useful for the next researcher who wants to do a research on foreign language especially in Tamil language.